1999
DOI: 10.1083/jcb.147.3.519
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Class Dhc1b Dynein in Retrograde Transport of Ift Motors and Ift Raft Particles along Cilia, but Not Dendrites, in Chemosensory Neurons of Living Caenorhabditis elegans

Abstract: The heterotrimeric motor protein, kinesin-II, and its presumptive cargo, can be observed moving anterogradely at 0.7 μm/s by intraflagellar transport (IFT) within sensory cilia of chemosensory neurons of living Caenorhabditis elegans, using a fluorescence microscope–based transport assay (Orozco, J.T., K.P. Wedaman, D. Signor, H. Brown, L. Rose, and J.M. Scholey. 1999. Nature. 398:674). Here, we report that kinesin-II, and two of its presumptive cargo molecules, OSM-1 and OSM-6, all move at ∼1.1 μm/s in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
281
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(297 citation statements)
references
References 59 publications
(127 reference statements)
12
281
1
3
Order By: Relevance
“…Here, we used a model organism, C. elegans. In C. elegans, 60 of the 302 neurons of the hermaphrodite are ciliated sensory neurons, and several works have demonstrated that the mutants of IFT-related genes show defects in sensory functions (Cole et al 1998;Signor et al 1999;Qin et al 2001;Haycraft et al 2003;Schafer et al 2003;Blacque et al 2004;Scholey et al 2004;Snow et al 2004;Ou et al 2005;Bell et al 2006;Evans et al 2006). In the present work, we identified nematode IFT-81 and IFT-74, whose C. reinhardtii orthologues were recently shown to form core complex in subcomplex B (Lucker et al 2005), and attempted to elucidate their physiological roles in C. elegans.…”
Section: Introductionmentioning
confidence: 96%
“…Here, we used a model organism, C. elegans. In C. elegans, 60 of the 302 neurons of the hermaphrodite are ciliated sensory neurons, and several works have demonstrated that the mutants of IFT-related genes show defects in sensory functions (Cole et al 1998;Signor et al 1999;Qin et al 2001;Haycraft et al 2003;Schafer et al 2003;Blacque et al 2004;Scholey et al 2004;Snow et al 2004;Ou et al 2005;Bell et al 2006;Evans et al 2006). In the present work, we identified nematode IFT-81 and IFT-74, whose C. reinhardtii orthologues were recently shown to form core complex in subcomplex B (Lucker et al 2005), and attempted to elucidate their physiological roles in C. elegans.…”
Section: Introductionmentioning
confidence: 96%
“…Consistent with an effect on cilia, some of these mutations affect genes that encode counterparts of complex A or B components of the Chlamydomonas IFT (for review, see Cole 2003). Moreover, on the basis of fusions of GFP with OSM-6, OSM-1, DAF-10, and others, IFT has been demonstrated for the cilia of the dendritic endings of the amphids and phasmids in C. elegans Signor et al 1999;Qin et al 2001;Blacque et al 2005;Ou et al 2005a,b).…”
mentioning
confidence: 94%
“…IFT in Chlamydomonas reinhardtii is dependent on the heterotrimeric kinesin II motor to transport ciliary cargo from the cell body to the tip of the cilium (anterograde IFT) (Kozminski et al , 1995; Cole et al , 1998; Qin et al , 2004; Hao et al , 2011; Craft et al , 2015), but in C. elegans and most likely also vertebrate cilia the heterotrimeric kinesin II cooperates with a homodimeric kinesin II motor for anterograde transport (Snow et al , 2004; Williams et al , 2014; Prevo et al , 2015). At the ciliary tip, exchange of the cargo and remodeling of the IFT complex take place and dynein 2 transports the IFT complex and recycling products back to the cell body (retrograde IFT) (Pazour et al , 1999; Porter et al , 1999; Signor et al , 1999; Qin et al , 2004). IFT is mediated by the IFT complex containing at least 22 protein subunits (organized into IFT‐A and IFT‐B subcomplexes), which likely mediates the interactions between IFT motors and ciliary cargo (Bhogaraju et al , 2013b).…”
Section: Introductionmentioning
confidence: 99%